EFFECT OF HONEY AND STEVIA AS SUGAR SUBSTITUTE ON SENSORY EVALUATION OF CHIFFON CAKE - Sanggramasari, Sandra (Institut Pariwisata dan Bisnis Internasional, 2019)
This research contributes to sugar substitution as a sweetener. Honey and stevia are natural sugar substitutes in various food products. The purpose of this research is to recognize the difference in appearance, flavour and texture of chiffon cake using sugar, honey and stevia. The research used an experimental method. This research used descriptive analysis technique of observation and interviews with reference to a comparison that is sensory evaluation of chiffon cake characteristic, which include appearance, flavour and texture. The results show that panelists prefer chiffon cake using sugar as a sweetener in terms of appearance and texture. However, chiffon cake using honey as a sugar substitute is preferable to panelists in terms of flavour and overall aspects.